THE IMPACT OF THE TECHNOLOGY ACCEPTANCE MODEL ON THE USE OF QR CODE PAYMENT AS A DIGITAL PAYMENT METHOD AMONG MSME ENTREPRENEURS IN THE CULINARY TOURISM CENTER OF SURABAYA - Firdausi, Nafilah Rahma; Antonio, Gregorius Rudy (jfpublisher, 2025)
Bank Indonesia introduced Quick Response Indonesian Standard (QRIS) to enhance digital transaction convenience, security, and efficiency, particularly to support MSMEs in boosting Indonesia's economy, although its adoption in the food and beverage industry remains limited. This research concentrates on the aspects that impact the willingness to use QRIS among MSME business owners in the Culinary Tourism Center of Surabaya, Indonesia through the lens of the Technology Acceptance Model (TAM). This causal study collected data from 50 MSME merchants over the age of 50 who had used QRIS as a payment method for more than a month. Using SEM-PLS analysis on SmartPLS 4.1, the research found that perceived usefulness significantly impacts the intention to use QRIS, leading to increased business productivity by enhancing transaction efficiency, reducing direct contact with clients, and improving payment security. The study also revealed that perceived ease of use does not directly influence the intention to use QRIS but affects it indirectly by enhancing perceived usefulness. The findings highlight the crucial role of perceived ease of use in shaping utility perception. The research contributes to the understanding of digital payment adoption among MSMEs in Indonesia, particularly in the food and beverage sector, by providing insights into the relationship between TAM variables. It emphasizes the need for targeted training and support to boost QRIS adoption, enabling MSME merchants to remain competitive in the digital economy. The study offers valuable recommendations for policymakers, financial institutions, and technological stakeholders to facilitate Indonesia’s economic digitalization through increased QRIS usage.